2009
DOI: 10.1002/hbm.20844
|View full text |Cite
|
Sign up to set email alerts
|

Tuning‐in to the beat: Aesthetic appreciation of musical rhythms correlates with a premotor activity boost

Abstract: Listening to music can induce us to tune in to its beat. Previous neuroimaging studies have shown that the motor system becomes involved in perceptual rhythm and timing tasks in general, as well as during preference-related responses to music. However, the role of preferred rhythm and, in particular, of preferred beat frequency (tempo) in driving activity in the motor system remains unknown. The goals of the present functional magnetic resonance imaging (fMRI) study were to determine whether the musical rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 84 publications
(126 reference statements)
5
95
1
4
Order By: Relevance
“…Interestingly, such oscillations are also associated with motor tasks (Fujioka, Trainor, Large, & Ross, 2009;Salenius & Hari, 2003). Consistently, the premotor activation in the brain is enhanced by listening to rhythms at one's preferred tempo (Kornysheva, von Cramon, Jacobsen, & Schubotz, 2010), and human listeners' preferred tempo in music (Moelants, 2002) corresponds to the preferred frequency (*2 Hz) in locomotion (Macdougall & Moore, 2005). These findings seem to suggest that the percept of regular pulse, which also defines the tempo, could entail a motor component: forming a pulse by means of entrainment may require a motor process, at least internally (Grahn & Rowe, 2009).…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, such oscillations are also associated with motor tasks (Fujioka, Trainor, Large, & Ross, 2009;Salenius & Hari, 2003). Consistently, the premotor activation in the brain is enhanced by listening to rhythms at one's preferred tempo (Kornysheva, von Cramon, Jacobsen, & Schubotz, 2010), and human listeners' preferred tempo in music (Moelants, 2002) corresponds to the preferred frequency (*2 Hz) in locomotion (Macdougall & Moore, 2005). These findings seem to suggest that the percept of regular pulse, which also defines the tempo, could entail a motor component: forming a pulse by means of entrainment may require a motor process, at least internally (Grahn & Rowe, 2009).…”
Section: Introductionmentioning
confidence: 87%
“…In support of this notion, individual trials have identified preferred characteristics in music that have an impact physical response. Kornysheva et al (2010) found that premotor activity is heightened when beat is preferred. Further, tempo preferences slow as we age, and capacity to entrain with non-preferred tempo is more challenging for older adults (McAuley et al, 2006).…”
Section: Meta-theorymentioning
confidence: 97%
“…Motion-capture studies illustrate this phenomenon, explaining spontaneous relaxation and contraction of muscles in response to tension, resolution and rhythm in music as an embodied form of music cognition (Burger, Thompson, Luck, Saarikallio & Toiviainen, 2013). Other research has focused on the influence of rhythm in music, demonstrating that patterns in bodily movements influence how rhythm is perceived (Phillips-Silver & Trainor, 2007) and that tempo and beat preferences have an impact on the magnitude of response (Kornysheva, von Cramon, Jacobsen & Schubotz, 2010;MacDougall & Moore, 2005;McAuley, Jones, Holub, Johnston & Miller, 2006). Further, neuroimaging research examining music listening demonstrates stimulation of the limbic and para-limbic structures in the brain corresponding with subjective feelings of motivation and reward (Koelsch, 2010), suggesting that music listening might have a positive influence on emotions during exercise.…”
Section: Introductionmentioning
confidence: 96%
“…Experimental work using fMRI scanners has given considerable insight into the parts of the brain that might facilitate entrainment. For example, Kornysheva, von Cramon, Jacobsen, and Schubotz (2010) highlighted the involvement of premotor and cerebellar brain sectors during preferred vs.…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 99%